Positive Massage: An Intervention for Couples’ Wellbeing in a Touch-Deprived Era - Sayuri M. Naruse; Mark Moss (European Journal of Investigation in Health, Psychology and Education, 2021)
COVID-19 has brought not only fear and anxiety, but also legitimate restrictions of communication and consequential touch-deprivation in our daily lives. Couples’ relational wellbeing continues to be impacted by these COVID-19 related stressors. Protecting both personal and relational wellbeing is therefore particularly important at this time. Using a preventative intervention approach, the current paper argues the theoretical benefit of the Positive Massage programme and reports a qualitative analysis of stressed but healthy couples’ experience of engaging in the programme. Thirty-four participants completed 3 weekly classes and home-based practice of massage exchange. Data from an open text online questionnaire completed every week of the programme and again 3 weeks afterwards were analysed using thematic analysis. The identified themes included “holistic stress relief”, “relationship-promotion”, and “selves-care skill”. Couples perceived Positive Massage as an effective mutual support skill to relax and help one another by de-stressing, both emotionally and physically through verbal and nonverbal communication, creating gratitude, deeper connection and self-efficacy via quality time together and pleasurable touch. Theoretically and experientially, Positive Massage can be an effective preventative selves-care skill. Promoting the concept of selves-care and its practical application through Positive Massage would be beneficial for couples’ personal and relational wellbeing in a touch-deprived era.